Narrative Finality - Armine Kotin Mortimer (Studies in 20th & 21st Century Literature, 1981)
The cloturai device of narration as salvation represents the lack of finality in three novels. In De Beauvoir's Tous les hommes sont mortels an immortal character turns his story to account, but the novel makes a mockery of the historical sense by which men define themselves. In the closing pages of Butor's La Modification, the hero plans to write a book to save himself. Through the thrice-considered portrayal of the Paris-Rome relationship, the ending shows the reader how to bring about closure, but this collective critique written by readers will always be a future book. Simon's La Bataille de Pharsale, the most radical attempt to destroy finality, is an infinite text. No new text can be written. This extreme of perversion guarantees bliss (jouissance). If the ending of De Beauvoir's novel transfers the burden of non-final world onto a new victim, Butor's non-finality lies in the deferral to a future writing, while Simon's writer is stuck in a writing loop, in which writing has become its own end and hence can have no end. The deconstructive and tragic form of contemporary novels proclaims the loss of belief in a finality inherent in the written text, to the profit of writing itself.
Keywords: cloturai device; narration; salvation; lack of finality; De Beauvoir; Tous les hommes sont morteles; self; identity; La Modification; Paris-Rome relationship; Butor; Simon; La Bataille de Pharsale; infinite text; infinity; jouissance; finality